Pengaruh Faktor Internal dan Eksternal Terhadap Kinerja Sistem Informasi: Studi Pada Perbankan - Lince Bulutoding; Antong Amiruddin (Journal of Accounting and Investment, 2014)
This research aims to examine the organization's internal and external factors on the performance of the accounting information system . The sample used is a banking company in the city of Makassar . Hypothesis testing is done by the method of multiple linear regression analysis . This study found internal factors that affect the performance of information systems is the size of the organization and support of top management. While, external factors that affect on performance information system is personal capability only.